2018
DOI: 10.1126/scisignal.aam9514
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating the overall stomatal response of plants: Rapid leaf-to-leaf communication during light stress

Abstract: The plant canopy functions as an aerial array of light-harvesting antennas. To achieve maximal yield, each leaf within this array and the array as a whole need to rapidly adjust to naturally occurring fluctuations in light intensity and quality. Excessive light stress triggers the closing of pores in leaves called stomata to minimize moisture loss. We found that different leaves within the canopy of an plant, including leaves not directly exposed to light, coordinated stomatal closure in response to light stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
225
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(230 citation statements)
references
References 44 publications
3
225
0
2
Order By: Relevance
“…a–d; Supporting Information Methods S1). While heat stress and dark‐to‐light transition initiated a rapid local and systemic stomatal opening responses, wounding induced rapid local and systemic stomatal closure responses, similar to the light stress‐induced local and systemic responses previously reported (Devireddy et al ., ). Taken together, the results shown in Fig.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…a–d; Supporting Information Methods S1). While heat stress and dark‐to‐light transition initiated a rapid local and systemic stomatal opening responses, wounding induced rapid local and systemic stomatal closure responses, similar to the light stress‐induced local and systemic responses previously reported (Devireddy et al ., ). Taken together, the results shown in Fig.…”
mentioning
confidence: 97%
“…Here it is shown that rapid local and systemic stomatal responses of Arabidopsis to excess light are dependent on the function of the serine/threonine protein kinase OST1, demonstrating that this systemic response could be dependent on ABA‐derived ROS production via OST1‐respiratory burst oxidase protein D (OST1‐RBOHD)‐mediated signaling, or ABA‐derived OST1–SLAC1 interactions (Fig. i; Devireddy et al ., ). As shown in Fig.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, it would be useful to investigate whether there was a systemic signal, such as the ROS wave, by investigating systemic leaf or whole plant ROS changes (e.g. Miller et al , ; Devireddy et al , ). For instance, Fichman et al () showed a whole plant increase in ROS when only one leaf was subject to either wounding or high‐light stress.…”
mentioning
confidence: 99%